Childhood IQ and Adult Mental Disorders: A Test of the Cognitive Reserve Hypothesis - Koenen, Karestan C. (2008)
OBJECTIVE: Cognitive reserve has been proposed as important in the etiology of neuropsychiatric disorders. However, tests of the association between premorbid IQ and adult mental disorders other than schizophrenia have been limited and inconclusive. The authors tested the hypothesis that low childhood IQ is associated with increased risk and severity of adult mental disorders. METHOD: Participants were members of a representative 1972-1973 birth cohort of 1,037 males and females in Dunedin, New Zealand, who were followed up to age 32 with 96% retention. WISC-R IQ was assessed at ages 7, 9, and 11. Research diagnoses of DSM mental disorders were made at ages 18, 21, 26, and 32. RESULTS: Lower childhood IQ was associated with increased risk of developing schizophrenia spectrum disorder, adult depression, and adult anxiety. Lower childhood IQ was also associated with greater comorbidity and with persistence of depression; the association with persistence of generalized anxiety disorder was nearly significant. Higher childhood IQ predicted increased risk of adult mania. CONCLUSIONS: Lower cognitive reserve, as reflected by childhood IQ, is an antecedent of several common psychiatric disorders and also predicts persistence and comorbidity. Thus, many patients who seek mental health treatment may have lower cognitive ability; this should be considered in prevention and treatment planning.